2007
DOI: 10.1002/lsm.20465
|View full text |Cite
|
Sign up to set email alerts
|

The 1,450‐nm diode laser reduces sebum production in facial skin: A possible mode of action of its effectiveness for the treatment of acne vulgaris

Abstract: Background and Objectives: Over the last several years, several light-based systems have been employed for the treatment of acne vulgaris. The 1,450-nm diode laser has been shown to improve acne, and this has been suggested to be due to effects on sebaceous glands. However, an effect on sebum production has not been demonstrated. The objective of this study was to evaluate if the 1,450-nm diode laser indeed reduces sebum production. Study Design/Materials and Methods: Eight patients with a history of acne were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
3
17
2
Order By: Relevance
“…7 One study proposed that the clinical effectiveness of the 1,450-nm diode laser may be based, at least in part, on the reduction in sebum production resulting from its effects on sebaceous glands. 8 Although the suppression of sebum production by this laser should theoretically lead to a decrease in P. acnes growth, we did not observe any reduction in fluorescence in the subjects as indirect evidence of P. acnes reduction under UV photographic study. The finding indicates that the clinical improvement from the 1,450-nm diode laser may result from mechanisms different from reducing the growth of P. acnes and the degree of suppression of sebum production was insufficient to decrease the growth of P. acnes.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…7 One study proposed that the clinical effectiveness of the 1,450-nm diode laser may be based, at least in part, on the reduction in sebum production resulting from its effects on sebaceous glands. 8 Although the suppression of sebum production by this laser should theoretically lead to a decrease in P. acnes growth, we did not observe any reduction in fluorescence in the subjects as indirect evidence of P. acnes reduction under UV photographic study. The finding indicates that the clinical improvement from the 1,450-nm diode laser may result from mechanisms different from reducing the growth of P. acnes and the degree of suppression of sebum production was insufficient to decrease the growth of P. acnes.…”
Section: Discussioncontrasting
confidence: 56%
“…The proposed mechanisms for the 1,450-nm diode laser in acne include selective photocoagulation of the sebaceous glands in the upper dermis, reduction of sebum production, and photothermal effect on inhibition of P. acnes growth. [7][8][9] Unlike blue light, with a pure photochemical effect, the longer wavelengths of the 1,450-nm diode laser can reach and thermally target the sebaceous structure at greater depth. The laser has been shown to induce thermal injury in the upper dermis histologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paithankar et al [6] have postulated that thermal damage created at the time of irradiation with the 1,450 nm laser may cause secondary functional impairment of the sebaceous gland, resulting in a reduction of sebum excretion. This hypothesis has been favored to explain the mechanisms of action of this laser, however to date few investigations have evaluated changes in sebum excretion rate (SER) after 1,450 nm diode laser treatment [8,9]. Although Jih et al showed a decrease in SER after 1,450 nm diode laser treatment using two treatment parameters (14 J/cm 2 vs. 16 J/cm 2 ), it has significant limitations in that it included no control site to account for diurnal and seasonal changes in facial SER [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that the 1,450-nm diode laser reduces sebum production in facial skin. 22 A fractional RF microneedle also showed a sebosuppressive effect in a prospective study of 20 Korean acne patients. 23 A recent uncontrolled clinical assessment study evaluated the efficacy of selective electrothermolysis of the sebaceous glands for the treatment of oily facial skin and showed a mean reduction rate of skin surface lipids of 31.5%.…”
Section: R E V I E W O F F a C I A L P O R E S D E R M A T O L O G I mentioning
confidence: 95%